Influence of modifying agents of organoclay on the properties of nanocomposites based on acrylonitrile butadiene rubber - E.M. Sadek; D.E. El-Nashar; S.M. Ahmed (Egyptian Journal of Petroleum)
Solvent blending of organoclay (OC) in polystyrene in combination with melt mixing with acrylonitrile butadiene rubber (NBR) are applied to provide acrylonitrile butadiene rubber/clay nanocomposites. Clay structures based on the prepared 1,12 dibromododecylhydroxyuronium and bromo dodecyl hydroxyuronium as cationic surfactants were prepared. Colloidal suspension of each organoclay in toluene was mixed separately with polystyrene giving two types of polystyrene-organoclay composites. The prepared polystyrene-organoclay PS-OC composites were characterized with X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform infrared (FTIR) spectroscopy. The results indicate the formation of polystyrene-organoclay composites with intercalated and partial exfoliated structures. The rheometric study demonstrate an increase in minimum and maximum torques with an increase in cure rate index (i.e. faster scorch and cure times) for the PS-OC (6 phr) incorporated NBR compound compared to unfilled NBR. This effect is more significant with NBR/PS-OC1 composites in comparison to NBR/PS-OC2 composites at the same loading indicating the nanoreinforcement effect of clay on the mechanical properties of these composites. Compounds filled with PS-OC1 exhibit higher tensile strength, Young’s modulus and less elongation at break compared to those compounds filled with PS-OC2. The higher stiffness of PS-OC1/NBR composites reflects the enhancement in hardness of these compounds with respect to those containing PS-OC2. Further increasing of PS-OC loading results in a significant decrease of the properties. This is due to a possible agglomeration formation of PS-OC in rubber matrix. Furthermore, the results of reinforcement of polymers with nanosized particles indicate a promising application of the organoclay and nanocomposites that affords high performance materials. Keywords: Acrylonitrile butadiene rubber (NBR), Nanocomposites, Cationic surfactants, Rheometric characteristics, Physico-mechanical properties